Low-voltage ride-through for a three-phase four-leg photovoltaic system using SRFPI control strategy - Haval Sardar Kamil; Dalila Mat Said; Mohd Wazir Mustafa; Mohammad Reza Miveh; Nasarudin Ahmad (Institute of Advanced Engineering and Science, 2019)
With the innovative progresses in power electronics in recent years, photovoltaic (PV) systems emerged as one of the promising sources for electricity generation at the distribution network. Nonetheless, connection of PV power plants to the utility grid under abnormal conditions has become a significant issue and novel grid codes should be recommend. The low-voltage ride-through (LVRT) capability is one of the challenges faced by the integration of PV power stations into electrical grid under abnormal conditions. This work firstly provides a discussion on recent control schemes for PV power plants to enhance the LVRT capabilities. Next, a control scheme for a three-phase four-leg grid-connected PV inverter under unbalanced grid fault conditions using synchronous reference frame proportional integral (SRFPI) controller is proposed. Simulation studies are performed to investigate the influence of the control strategy on the PV inverter.